EFFECTIVENESS OF USING GRAPHIC ANIMATION COURSEWARE FOR STUDENTS WITH DIFFERENT COGNITIVE STYLES AND SPATIAL VISUAL ABILITIES - Madar, Ahmad Rizal; Hashim, Mohd Noor (Journal of Technical Education and Training, 2011)
This research was conducted to examine the effectiveness of using graphic animation courseware on pre and post test performance achievement in Electronic System 1 subject among students undergoing Certificate of Electrical and Electronic Engineering at the Malaysian Ministry of Higher Education Polytechnics. These students have different Cognitive Styles (Field Independent & Field Dependent) and Spatial Visual Abilities (High Visual and Low Visual). The achievement performance of this pre and post test was obtained from students who apply graphic animation courseware (experimental group) and conventional (control group) as their learning styles. The research samples comprised of 138 semester 1 students undergoing Certificate of Electrical and Electronic Engineering in the Department of Electrical Engineering, MOHE polytechnics. Two MOHE polytechnics were involved in this research, which are Central and Southern Zone. The experimental group consisted of students from Southern Zone, while the control group recruited students from Central Zone. Quasi-experimental with 2 x 2 factorial (Cognitive style x spatial visual ability) design was applied using quantitative data. Data collected were analysed using descriptive and inferential statistics which are mean, standard deviation, and independent samples T-test. A significant value of 0.05 was set for data reporting. Overall research finding shows that ; there was a significant difference in students achievement with Cognitive Styles of FI, FD, VT and VR where the experimental group were found better than the control group ; there was significant differences in the achievement of students with the characteristics of FIVT, FIVR, FDVT and FDVR where the experimental group showed a better result compared to the control group and ; the elements (Interface Design, Interaction Design, Motivation and User Friendliness) in the Electronic System 1 graphic animation courseware assist in students learning achievement. Overall, graphic animation courseware has the potential to improve students’ achievement where those with the FIVT, FI and VT characteristics, will be benefited most.